CARDIAC SURGERYRisk factors for paravalvular leak after transcatheter aortic valve implantation - Wilczek, Krzysztof; Bujak, Kamil; Reguła, Rafał; Chodór, Piotr; Osadnik, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Many studies have shown that transcatheter aortic valve implantation (TAVI) improves outcomes in patients with severe aortic stenosis in whom a classical surgical procedure cannot be performed due to the high risk. As one of the most frequent periprocedural complications of TAVI, paravalvular leak significantly affects the short- and long-term prognosis for patients undergoing implantation. In this paper, we analyze the most significant anatomical and procedural predictors of paravalvular leak after TAVI.